Determining characteristic sand shear parameters of strength via a direct shear test - Skuodis, Šarūna; Norkus, Arnoldas; Dirgėlienė, Neringa; Rimkus, Liudvikas (Journal of Civil Engineering and Management, 2016)
The article considers the peculiarities of determining quartz sand shear strength according to the Mohr-Coulomb strength criterion, via a direct shear test and that of factors influencing the characteristic angle of internal friction and cohesion values of the obtained strength parameters. The air-dry sand of the Baltic Sea region from Lithuanian coastal area near Klaipėda city has been analyzed. The solid density of the investigated sand grains was ρs = 2.65 g/cm3. The initial density of the tested samples made 1.48–1.50 g/cm3. Processing data on the shear test yielded that the quantity of 18 tests was sufficient for the relevant accuracy of determining characteristic sand shear parameters of strength. This quantity of tests allow avoiding the influence of statistical coefficient tα that depends on a degree of freedom (K = n – 2). The paper presents additionally analyzed three different approaches to determining the characteristic shear parameters of strength and that of a comparative analysis of the applied approaches.